Character Education Through the Constructivist Design of Islamic Education Subject at Elementary School Pembangunan Jaya II in Gedangan Sidoarjo - Rusydiyah, Evi Fatimatur (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
The objective of this study are (1) to determine the meaning of character education in the elementary school of Pembangunan Jaya II of Gedangan Sidoarjo, (2) to identify how the planning of character education through constructivist design on the Islamic education subjects in the elementary school of Pembangunan Jaya II of Gedangan Sidoarjo. Observation, in-depth interviews and documentation analysis were used in this study. The finding showed that: (1) elementary school Pembangunan Jaya II in Gedangan Sidoarjo has developed character education. The character education that is developed is fond of learning character, creative character, independent character and noble, (2) constructivist design that is developed by SD Pembangunan Jaya II Gedangan Sidoarjo has a component in accordance with the constructivist theory, namely, engage, explore, explain, extend, and evaluate. By the application of habituation based on the constructivist design make the students to have the attitude of eager to learn, creative, independent, and noble character in accordance with the main purpose of the school. Copyright © 2014 by Al-Talim All right reserved